THE IMPORTANCE OF LEARNING FOREIGN LANGUAGES IN THE MODERN WORLD - Atham Ziyodullayev; Madina Neʼmatova Baxtiyor qizi (TADQIQOTLAR, 2025)
Abstract: This paper examines the importance of learning foreign languages in today’s globalized world. Foreign language competence enhances communication skills, broadens cultural understanding, and increases academic and professional opportunities. The study explores how multilingualism contributes to cognitive development, intercultural communication, and competitiveness in the international labor market. Additionally, it highlights the role of modern technologies and innovative teaching methods in the process of language learning. The findings emphasize that learning foreign languages is an essential requirement for successful integration into global society.